The Flowshop Scheduling Makespan by the ACO-GA Algorithm: The Flowshop Scheduling Makespan by the ACO-GA Algorithm - Jonas Franky R Panggabean; Opim Salim Sitompul; Erna Budhiarti Nababan (Jurnal Mantik, 2020)
Flow shop scheduling could be a scheduling model where all jobs that are processed flow within the same direction / path. the matter is usually faced if n jobs are processed on m machines, where what must be done first and what allocates jobs on the machine in order that a scheduled production process are obtained. To validate this algorithm a computational test was done employing a dataset of 60 examples from the Taillard Benchmark. HS algorithm with a comparison of two constructive heuristics from the literature, namely the NEH heuristic and stochastic greedy heuristic (SG). The average results obtained for dataset sizes are 20 x 5 to 50 x 10, that the ACO-GA algorithm has smaller makespan compared to the opposite two algorithms, except for large dataset sizes the ACO-GA algorithm has larger makespan compared to the 2 algorithms above with difference of 1.4 units of your time